Good Governance Principles and Technology on Employee Performance: A Literature Review - Fadhilah; Reni Oktavia; Usep Syaipudin (PT FORMOSA CENDEKIA GLOBAL, 2024)
This literature review examines the interplay between good governance principles in enhancing employee performance within Indonesia's public sector. Following the enactment of pivotal laws in 2004, local governments gained autonomy in managing financial resources, underscoring the importance of good governance to meet societal expectations. Despite a robust theoretical framework, public skepticism persists regarding local government performance, emphasizing the necessity for continuous improvement. This study synthesizes research from 2019 to 2024, highlighting both the enabling factors and challenges of integrating technology into governance practices. The findings reveal that effective technological integration can streamline processes and enhance accountability, ultimately fostering improved public service delivery. However, challenges related to infrastructure, training, and data privacy must be addressed. The review calls for a tailored, holistic approach that aligns governance principles with technological and organizational factors to optimize performance in Indonesia's public sector